In Situ Transmission X-ray Micro-Diffraction from Thin Metal Films Electrodeposited in Microfluidic Channels. Issue 11 (14th July 2020) - Wiegmann, T.; Drnec, J.; Reikowski, F.; Stettner, J.; Maroun, F.; Magnussen, O. M.
Abstract : High-energy X-ray surface diffraction in transmission geometry is combined with a microfluidic thin layer flow cell for in situ studies of the local structure of electrodeposited epitaxial films. The capabilities of this approach are illustrated using Bi films on Au(100) single crystals as an example. We demonstrate that the local film thickness, the strain, and the orientation of the deposits' crystallites can be mapped with a spatial resolution of a few micrometers. The high heterogeneity of the Bi films provides deposits with a wide range of structural properties, allowing to establish correlations between the different parameters as a function of the local thickness.